Luid ka, Clark: a morphological landscape mapping method for documenting memoryscapes in the landscape context of identified historical places in Clark Freeport Zone - Diaz, Cathleen Carpio (College of Architecture, University of the Philippines Diliman, 2025)
This thesis examines the transformation of Clark Freeport Zone (CFZ) from a former U.S. military base to a major economic zone, with a focus on documenting its cultural memory amidst rapid urban modernization. While CFZ's Design Standards and Guidelines (DSG) emphasize economic growth and urban competitiveness, they provide limited provisions for heritage and memory conservation, raising concerns about the weakening of CFZ's historical identity.